High-Resolution Adaptive Optics Retinal Imaging of Cellular Structure in Choroideremia - Morgan, Jessica I. W.; Han, Grace; Klinman, Eva; Maguire, William M.; Chung, Daniel C.; Maguire, Albert M.; Bennett, Jean (Investigative ophthalmology & visual science, 2014)
We characterized retinal structure in patients and carriers of choroideremia using adaptive optics and other high resolution modalities. A total of 57 patients and 18 carriers of choroideremia were imaged using adaptive optics scanning light ophthalmoscopy (AOSLO), optical coherence tomography (OCT), autofluorescence (AF), and scanning light ophthalmoscopy (SLO). Cone density was measured in 59 eyes of 34 patients where the full cone mosaic was observed. The SLO imaging revealed scalloped edges of RPE atrophy and large choroidal vessels. The AF imaging showed hypo-AF in areas of degeneration, while central AF remained present. OCT images showed outer retinal tubulations and thinned RPE/interdigitation layers. The AOSLO imaging revealed the cone mosaic in central relatively intact retina, and cone density was either reduced or normal at 0.5 mm eccentricity. The border of RPE atrophy showed abrupt loss of the cone mosaic at the same location. The AF imaging in comparison with AOSLO showed RPE health may be compromised before cone degeneration. Other disease features, including visualization of choroidal vessels, hyper-reflective clumps of cones, and unique retinal findings, were tabulated to show the frequency of occurrence and model disease progression. The data support the RPE being one primary site of degeneration in patients with choroideremia. Photoreceptors also may degenerate independently. High resolution imaging, particularly AOSLO in combination with OCT, allows single cell analysis of disease in choroideremia. These modalities promise to be useful in monitoring disease progression, and in documenting the efficacy of gene and cell-based therapies for choroideremia and other diseases as these therapies emerge. (ClinicalTrials.gov number, NCT01866371.).